Konsep Judicial Review terhadap Undang-Undang di Indonesia: Perspektif Siyāsah Dustūriyyah dan Otoritas Ahl al-Ḥall wa al-‘Aqd - Wiwin Guanti (Cendekia Inovatif Dan Berbudaya, 2026)
This research examines the conceptual intersection between the judicial review mechanism in Indonesia and the Siyāsah dustūriyyah perspective on monitoring legislative products. Indonesia's constitutional transition toward constitutional supremacy positions the Constitutional Court (MK) as the guardian of the constitution, whereas in Islamic constitutional law, the Wilāyat al-maẓālim institution oversees legislation produced by ahl al-ḥall wa al-‘aqd (AHWA). Utilizing a normative legal research method with statutory, conceptual, and comparative approaches, this study aims to extract and synthesize the philosophical foundations of both legal systems. The results indicate that the existence of the Constitutional Court is a modern manifestation of Wilāyat al-maẓālim, functioning to evaluate legislative products (laws) to ensure they do not conflict with the highest norms. To perform this function optimally and prevent new forms of oppression, the constitutional judicial institution must utilize capability (al-quwwah) and moral integrity (al-amānah) to ensure the establishment of substantive justice according to Ibn Taymiyyah's principles. In conclusion, the concept of judicial review in positive constitutional law and Siyāsah dustūriyyah does not experience an ontological or epistemological clash, but rather symmetrically combines to limit state apparatus arbitrariness, guarantee human rights, and uphold justice.